POLA ASUH ORANG TUA BERPROFESI MILITER DALAM MEMBANGUN KEMANDIRIAN ANAK (Studi Kasus pada Anak Usia Tahun di Kelurahan Mekarwangi Kecamatan Tarogong Kaler Kabupaten Garut) - Winka Tirsa Aulia, - (2023)
Independence is very important in a person's life. Children's independence makes them more responsible in realizing their goals and strengthens children's self-confidence. one of them is influenced by parenting. Many people assume that authoritarian parenting styles are always applied by families with a military background. This is because families with a military background are known to uphold the value of discipline that comes from the guidance of the head of the family in carrying out their duties as members of the military. The purpose of this study is to find out what parenting patterns are used by parents with military profession in building children's independence, knowing the independence of children who have parents with military profession and the difficulties of parents with military profession in building children's independence. this research uses a qualitative approach that seeks to describe something in accordance with the facts with the case study method where the case study method is one of the scientific parts of the research. This study found that the type of parenting pattern applied by military parents in building children's independence is dominated by democratic parenting, which is considered wiser and more conducive in developing children's independence, where this parenting pattern also gives freedom to children with certain restrictions. Although there are still applications of other parenting patterns such as the application of authoritarian and permissive parenting. For the independence of 4-year-old children with military parents, it is known that each aspect of deveopment has begun to develop and in terms of taking care of children, military parents in building the independence of 4-year-old children stated that they did not find it difficult to build children's independence because it was their responsibility and obligation to their children. Keywords: Children's independence, parenting patterns, military parents